A bibliometric analysis of publications of library marketing: based on Google Scholar publication from 2017 to 2022 - Gunarathna, D.G.R.L.; Kumara, H.U.C.S.; Karannagoda, Neluka Maduranga (University of Colombo, 2023)
In order to effectively inform and educate existing and potential library users about the varying resources and services available to meet their specific needs and interests, library marketing is essential. Mastery of marketing skills is essential not only to raise awareness about the intrinsic value of the library but also to expand its user base. This study is significant as it provides library marketing scholars with a consolidated data set for future research. As such, this study utilized Google Scholar as its foundational source of data to analyze the spectrum of research outputs within the field of library marketing. In addition to this main objective, it delved into the dynamic growth trajectory in library marketing research publications. The research further explored country-specific contributions, revealing the global landscape of library marketing research. The study also examined the various types of libraries that were the focus of these publications. The bibliographic analysis is the methodology used in the study. The study was limited to using the keyword "Library Marketing" in publish or perish software's "Keyword" tag. The data was limited to years, 2017 to 2022, using the "Years" range tag. This study engaged with 246 publications, and the data retrieval process was done through the "Publish or Perish" software, harnessing the extensive prowess of Google Scholar. Data analysis and visualization were complemented by VOSviewer software and MS Excel package. During this intensive exploration, the following illuminating insights emerged. India led the global contributors with 55 publications (22%), followed by the United States with 40 publications (16%), and Nigeria with 35 publications (14%). In 2022, 49 articles (20%) were published, representing a significant increase over the previous year. There was a strong focus on University Libraries, resulting in 111 publications (45%). Scholarly journals emerged as the prime breeding ground for these insights, with 193 articles (78%) emerging from this field. This research has reverberations across the scholarly landscape, providing researchers with a solid foundation for venturing into the uncharted territory of library marketing. The study recommended additional research based on the index journals database to gain greater insight into publications related to library marketing. Additionally, models, concepts, and technology supporting marketing are recommended for future studies.
Keywords: library marketing; bibliometric analysis; Google scholar; Publish or Perish; VOSviewer